LEVEL STUDENTS INTEREST IN LEARNING SPEAKING BY UTILIZING PODCASTS THROUGH INQUIRY STRATEGYAT SMKN 4 - Hardiyana Hardiyana; Ammang Latifa; Salasiah Ammade (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2021)
Technology has produced prominent contribution on education in this information age, it is well known as Edu technology. The researcher tries to introduce an alternative media, namely podcasts. Podcast is one of interactive media applied to support learning process in the classroom in developing listening and speaking skills. A descriptive quantitative method was conducted by the researcher in this study. The population was the XI Grade of SMK 4 Sidrap. Due to this semester only consisted one intact class (20 students), the researcher used the cluster sampling method in deciding the research sample. The instruments that were used in collecting the data Liker’s scale questionnaire. The result of the data found was analysed by using SPSS Application. The students stated interested in learning speaking toward podcast. It was proved by the mean score of students’ interests was 55.40 and considered as moderately interested.